SMART and TOPSIS Method For Determining The Priority Of Screen Printing - Setiawan, Rinaldi; Arini, Arini; Wardhani, Luh Kesuma (Politeknik Ganesha Medan, 2020)
The number of micro, small and medium enterprises (MSMEs) in the field of screen printing and convection that use websites in marketing is one of them CV. Ini Sablon. but in the production process there are obstacles in working on orders that come to be done first in accordance with predetermined criteria, namely deadlines, number of orders, design, profit, and availability of goods. The use of Decision Support System (DSS) aims to provide recommendations to owners of screen printing companies. This study uses the SMART method to weight the criteria and the TOPSIS method for product selection. This system is built using the PHP programming language and MySQL database. The results of the study were a screen printing production priority website with the best final value of 0.62 and the worst final value of 0.35 with the level of accuracy between manual and system calculations reaching 100%. In this study the criteria cannot be updated, it is expected that further research criteria can be updated and use a combination of methods that have not been done.